A tiered approach for environmental impact assessment of chemicals and their alternatives within the context of socio-economic analyses. (1st December 2015) - Bruinen de Bruin, Y.; Peijnenburg, W.; Vermeire, T.; Posthuma, L.; Hogendoorn, E.; Verhoeven, J.
Abstract: The European Union's REACH regulation has introduced Socio-Economic Analyses as a new decision support tool in the domain of chemical policy-making. This paper presents a pragmatic method to review the replacement of chemicals in processes or products in terms of the environmental impact. The aim of this work is to develop a broadly accepted method for environmental impact assessment as part of Socio-Economic Analyses. The method consists of a stepwise and tiered approach for Environmental Impact Assessment whereby the expected impact of the replacement of chemicals is assessed via Risk Characterization Ratios and toxic pressure quantification (expressed as a Potentially Affection Fraction of species), and – if relevant – via a Persistency, Bioaccumulation potential and Toxicity score. The working of the method is demonstrated by the replacement of chemical substances in detergents, gutters and Expanded Polystyrene. Of the three replacements, for gutters, the reduction of the toxic pressure on the aquatic compartment was highest. Based on 50% effect concentrations the Potentially Affection Fraction of species due to the use of zinc gutters was relatively high (15%), while it was 0.6% after replacement by PVC gutters. This indicates that PVC gutters have a lower direct impact on aquatic biodiversity than zinc gutters. This paper demonstrates that even with limited data the proposed method can be used to move from risk indicators to impact indicators. The tiered approach allows finding the most appropriate level of analysis in a cost and resource efficient way. The method allows comparison of results of different scenarios and as such allows selecting the most preferable alternative from an environmental perspective. This is useful in the context of socio-economic analysis and as such, this method is available as a decision-support tool under REACH and other chemical policy frames such as the United Nations Environment Program. Highlights: A tiered method is developed for environmental impact assessment of chemicals. The method enables time and cost efficient analysis at limited data availability. The method is applied to three case studies of hazardous chemical replacement. The method provides results useful in the context of socio-economic analysis. The method is useful as decision-support for REACH and other chemical policy frames.